2012
DOI: 10.1111/cpf.12007
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxidative stress is induced by single‐sprint anaerobic exercise in young cigarette smokers

Abstract: Cigarette smoking increases oxidative stress, which is a risk factor for several diseases. Smoking has also been reported to enhance plasma oxidative stress during strenuous exercise. However, no prior study has examined the changes in plasma oxidative stress after single-sprint anaerobic exercise in cigarette smokers. The purpose of this study was to investigate these changes in young cigarette smokers by measuring reactive oxygen species generation and total antioxidant content. Participants were 15 male smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Exercise-induced oxidative stress is also increased by cigarette smoking. Indeed, multiple studies have found that plasma oxidative stress after strenuous exercise is higher in smokers than in nonsmokers11, 13 ) . However, these effects have not been examined following moderate-intensity exercise, which is optimal for promoting health, improvement of physical fitness, and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exercise-induced oxidative stress is also increased by cigarette smoking. Indeed, multiple studies have found that plasma oxidative stress after strenuous exercise is higher in smokers than in nonsmokers11, 13 ) . However, these effects have not been examined following moderate-intensity exercise, which is optimal for promoting health, improvement of physical fitness, and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers refrained from smoking cigarettes for 12 h before the study to avoid the acute effects of cigarette smoking on hydroperoxide concentrations in plasma and hydrogen peroxide (H 2 O 2 ) concentrations in exhaled breath condensate (EBC)3, 12, 13 ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaerobic exercise is followed by an increase in lipid peroxide concentration and the total antioxidative capacity of blood plasma, which indicates disruptions to the prooxidant antioxidant balance [ 19 ]. Even though research has observed the activation of the κB nuclear factor in the nuclei of peripheral blood mononuclear cells [ 20 ], enzymatic antioxidant defense has not yet been unambiguously shown to have a significant role in preventing the development of oxidative stress following anaerobic exercise.…”
Section: Introductionmentioning
confidence: 99%